EXPLORING GRAMSCI’S REFLECTIONS: AN ANALYSIS OF PRISON NOTEBOOKS - Elias Garcia, Tatiane (Revista Gênero e Interdisciplinaridade, 2024)
The arrest of Antonio Gramsci in 1926 was a landmark event in the political history of 20th century Italy. As Mussolini’s fascist regime consolidated its power, Gramsci, a communist leader and prominent intellectual, was detained due to his influence on the political opposition. His arrest was part of a campaign to suppress dissent. Despite facing adverse conditions in prison, Gramsci continued his intellectual production, writing the “Prison Notebooks”, a testament to his erudition and resilience. His arrest and production of the “Notebooks” highlight the power of intellectual resistance and commitment to social justice.